RFID Reader Antennas For Tag Detection in Self-Confined Volumes at UHF - C. R. Medeiros; Costa, J. R.; C. A. Fernandes (IEEE Antennas and Propagation Magazine, 2011)
Confinement of the detection region is a critical issue for some important RFID applications, where the coarse location of the object is required along with its identification. In the UHF band, it is a challenge to confine antenna radiation to reasonably sharp interrogation volumes, <10 lambda(3),without resorting to physical barriers. This paper presents a novel approach for RFID reader radiating structures that self-confine tag detection to a desired volume, avoiding undesired readings outside the interrogation volume. The proposed solution simultaneously covers the three world-assigned RFID frequency subbands at UHF. To demonstrate the effectiveness of the solution, the proposed configuration was integrated into bookshelves, a conveyor belt system, and a proximity point reader. Together with an appropriate control application, these form the building blocks of a smart store with automatic inventorying and billing capability. The radiating structure concept was explored by full-wave simulations, and it was validated with both near-field measurements and with tag-reading scores. Short demonstration videos are available online.